2014
DOI: 10.1080/14786419.2013.869692
|View full text |Cite
|
Sign up to set email alerts
|

Furtherin vitroevaluation of antiradical and antimicrobial activities of phytol

Abstract: The antiradical activity of phytol was evaluated by electron paramagnetic resonance towards hydroxyl radical (·OH), superoxide anion radical (·O2(-)), methoxy radical (·CH2OH), carbon-dioxide anion radical (·CO2(-)), as well as towards nitric-oxide radical (·NO) and 2,2-diphenyl-1-picrylhydrazyl (·DPPH) radical. It reduced the production of all tested radicals showing more promising activity against ·CO2(-), ·CH2OH and ·DPPH radicals (56%, 50% and 48%, respectively) in comparison with ·NO, ·O2(-) and ·OH radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
86
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(88 citation statements)
references
References 29 publications
0
86
0
2
Order By: Relevance
“…Limonene present in appreciable amounts (5.66%) in our oil efficient in inhibiting the proliferation of a variety of microorganisms that cause food spoilage [49] . The antimicrobial activity of phytol against eight bacterial and eight fungal strains was investigated by Pejin et al [50] . It was proven that phytol to be active against all tested bacteria and fungi.…”
mentioning
confidence: 99%
“…Limonene present in appreciable amounts (5.66%) in our oil efficient in inhibiting the proliferation of a variety of microorganisms that cause food spoilage [49] . The antimicrobial activity of phytol against eight bacterial and eight fungal strains was investigated by Pejin et al [50] . It was proven that phytol to be active against all tested bacteria and fungi.…”
mentioning
confidence: 99%
“…Otherwise, ROS coming from the substances may implicate DNA damage; one of them is the • OH which eventually binds with metal ions randomly distributes in the DNA; the ultimate result is the single strand break (SSB) [7], whichever also evident for oxidative DNA modification [13]. Pejin et al [14] suggested that PYL is a potent radical scavenger, which potentially scavenged…”
Section: Discussionmentioning
confidence: 99%
“…20 Phytol is found common in both the species. Phytol is an important phytochemical compound having properties as an anxiolytic, anti-depressant, 21 anti-radical, 22 antibacterial, 23 anti-cancer, 24 anti-inflammatory. 25 Thus the abundant presence of phytol in leaves of Allophylus species suggests that these species may prove helpful in prevention of degeneartive diseases.…”
Section: Plate 2: Chromatogram Of Gcms Analysis Of Young Leaves a Sementioning
confidence: 99%
“…15 There are some reports on phytochemical studies of A. cobbe. Screening of leaves and barks of A. cobbe gave Phytol is used in the fragrance industry and used in cosmetics, shampoos, toilet soaps, household cleaners, and detergents [28] anti-cancer [24] antimicrobial [23] anti-radical [22] anti Abbrv-RT-Retention Time, %Conc.-percent concentration, MW-Molecular weight, MF-Molecular formula *-literature not found.…”
mentioning
confidence: 99%